Multiple structures and transition mechanisms of laminar fuel-rich ethanol/air counterflowing spray flames - Ying, Zhaoping; Gutheil, Eva (International journal of spray and combustion dynamics, 2023)
Structures of laminar non-premixed ethanol/air spray flames in the axisymmetric counterflow configuration are studied under fuel-rich conditions by means of numerical simulations. The monodisperse ethanol spray is carried by air and directed against an air stream. Both streams enter at 300 K, and the system is at atmospheric pressure. Up to three different structures of these flames for identical boundary and initial conditions are identified, and regime diagrams are presented that show their conditions of existence in terms of the gas strain rate on the spray side of the configuration, - a−∞ - , starting from 55/s at an initial spray velocity of 0.44 m/s. The equivalence ratio on the spray side, - E−∞ - , is varied between 1.1 and 1.6, and initial droplet radii, - R0 - , from 10 to 50  - μ - m are considered. The most stable spray flame structure is characterized by two chemical reaction zones. For some conditions, single chemical reaction zones on either side of the counterflow configuration are found. Conditions under which these different flame structures exist are analyzed. Previous studies identified only two different structures for non-identical boundary conditions, and in this study, three different structures are presented for the first time. Moreover, the transition mechanisms of one structure to another are analyzed. The competition between the energy-consuming spray evaporation and the exothermic chemical reaction rates as well as the location of the spray determines the existence of the different flame structures. This transition of the different flame structures may explain spray flame characteristics such as flame pulsation or flame instabilities.